Feasibility of total polar compound and its five components to evaluate the deterioration of heated and fried oil: Aspect of regulations of various countries. (15th December 2022) - Li, Xu; Wang, Zhisheng; Xing, Changming; Chen, Zike; Sun, Wenxing; Sun, Cong; Xu, Guangfei; Wang, Xingguo
Abstract: This work discussed the feasibility of total polar compounds (TPC) and its five components to evaluate the deterioration of heated and fried oil from correlation, characteristic composition, and regulation aspects. Results showed that the TPC, oxidized triglyceride oligomer and dimer (TGO + TGD), and monomer (oxTGM) could be individually used to evaluate the deterioration of heated oil ( P < 0.01), while the quality control of fried oil required both TPC and oxTGM. The TPC index, currently regulated by most countries, has not achieved the supervision of oxTGM in fried oil ( P > 0.05). But at discarding points of TPC 24%, 25%, and 25%, oxTGM content in fried oil was as low as 3.5–3.6 g/100g, while diglyceride (DG) content (hydrolysis products or possibly broken oxTGM) reached 9.0–11.0 g/100g. The effectiveness of relevant regulation settings in different countries was also re-evaluated. The health effect caused by oxTGM and DG may be a problem that raised worldwide concern. Highlights: TPC, (TGO + TGD) and oxTGM can be individually used to evaluate heated oil. Both TPC and oxTGM were required for the quality control of fried oil. TPC has not achieved the supervision of oxTGM in oil during frying. Effectiveness of regulation settings in different countries was re-evaluated.